ECONOMIC ANALYSIS OF DAIRY ANIMAL DISEASES IN PUNJAB: A CASE STUDY OF FAISALABAD DISTRICT - M. Ashfaq; A. Razzaq; Shamsheer-ul-Haq; G. Muhammad (Journal of Animal and Plant Sciences, 2015)
This study estimates the prevalence of key livestock diseases in district Faisalabad and evaluates the effects they have on livestock productivity and farm incomes. Particular focus of the study is on the negative consequences on milk production and farm incomes due to mastitis, Parturient Hemoglobinuria, Foot and Mouth Disease (FMD), and tick infestations. The economic losses associated with these diseases are estimated. The analysis of diseases shows that the morbidity rate of tick infestation and FMD is high both in buffaloes and cows, and significant economic losses are being caused by these diseases due to reduced milk production, weight loss, and abortion. The production of milk can be enhanced, and per animal and per farm income can be increased, by controlling for these diseases. The economic losses caused are proportional to the scale of farming. However, on a per animal basis the losses are generally higher for small and medium farms than for large farms. The share of livestock income in total farm income is around 50 percent which makes this sector vital to the survival of the farming community, especially the small farmers. With the help of proper training, extension services, and veterinary care facilities, these diseases can be controlled, and the dairy business improved, thereby lifting the overall agriculture sector of Pakistan.
Keywords: Economic analysis; dairy animal diseases; farm income; benefit-cost ratio; Pakistan